Familial multiple fetal cerebral arteriovenous malformations: a case report of maternal genetic susceptibility and fetal manifestation - Wang, Hao; Jiang, Yan; Chen, YanLin; Chen, GongLi (Frontiers in Genetics, 2026)
IntroductionCerebral arteriovenous malformations (AVMs) are rare vascular anomalies that can present significant clinical challenges, especially when occurring in multiple sites. Hereditary hemorrhagic telangiectasia (HHT), a genetic disorder may be caused by mutations in genes such as ENG (encoding endoglin) or ACVRL1 (ALK1), and less commonly SMAD4, is one condition that predisposes individuals to multiple AVMs. This case report investigates the role of maternal genetic susceptibility in the fetal manifestation of multiple cerebral AVMs.Case PresentationA multiparous woman with embolized pulmonary AVMs underwent high-resolution fetal neurosonography at 29+4 weeks for maternal HHT risk and third-trimester screening flags (prominent venous structures). Targeted ultrasound revealed multiple cerebral AVMs with a dilated superior sagittal sinus. Trio-exome identified a heterozygous ENG variant in the mother, Sanger-confirmed and present in the fetus, consistent with direct genetic predisposition. Limb/ear minor anomalies (polydactyly, accessory auricle) prompted syndromic re-analysis (CM-AVM, JP-HHT overlap, PI3K-pathway, GLI3), which was negative for additional diagnostic variants.ConclusionThis case strengthens the link between familial ENG-mediated HHT and fetal cerebral AVMs, underscores the value of targeted third-trimester neurosonography in at-risk pregnancies, and clarifies variant-level evidence supporting causality.